The Effect of Acceptance and Commitment Therapy on Health Related Beliefs in Patients with Type 2 Diabetes - Safieh Abdollahi; Mohammad Hatami; Fardin Moradi Manesh; Parviz Asgari (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2020)
Aim and Background: Diabetes is a factor of many physical and psychological disorders. Nowadays, the concept of adherence in diseases be attention and has been developed due to changing the illness pattern from acute to chronic, changing its ideology from cure to prevention, limited economical resource and shortening the Duration of hospitalization of patients. In order to, the aim of this study was to survey of effectiveness of acceptance and commitment therapy on health related beliefs among patients with type 2 diabetes.